THE DEVELOPMENT OF E-MODULE ON SUBJECT OF STATISTICS IN STUDY PROGRAM CIVIL ENGINEERING EDUCATION, UNIVERSITAS NEGERI JAKARTA - Ramadhan, M. Agphin; Murtinugraha, R. Eka (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
The purpose of this research is to develop an e-module for the Statistics subject in the Building Engineering Education study program, Jakarta State University. E-module development using Adobe InDesign software. This research is included in development research (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, dan Evaluation). Two experts, who are material experts and media experts, validate the product. The product is an e-module which consists of 6 modules. Based on the validation, the average score of the material expert's assessment of modules 1 - 6 was 84% in the very feasible category. The average score of the media expert's assessment of modules 1 - 6 is 88.67% in the very feasible category. Based on the results of the validation, the Statistics E-Module is very feasible to use.